Can mobility on demand bridge the first-last mile transit gap? Equity implications of Los Angeles' pilot program. (June 2021) - Brown, Anne; Manville, Michael; Weber, Alexandra
Graphical abstract: Highlights: Do ride-hail transit partnerships boost transit access for vulnerable populations? Trip and survey data used from LA Metro's Mobility-on-demand (MOD) Sandbox pilot. More MOD users are white and have smartphone and banking access vs average riders. MOD successfully operated but did not increase transit access for marginalized users. Program design and evaluation metrics need to focus on equity-based outcomes. Abstract: Transit agencies and advocates see removing or bridging the first-last mile gap as an important way to increase transit ridership and reduce vehicle use. Some transit agencies see the advent of ride-hail services like Uber and Lyft as an opportunity for a nimble and flexible solution to first-last mile problems able to deliver more riders to and from transit stations. While agencies across the US have piloted such programs, limited evaluation to date means the outcomes of such partnerships remain unknown. Using just over a year of trip data from the Los Angeles Metro Mobility on Demand (MOD) pilot program, we answer two related questions about ride-hailing and transit access: first, do people use ride-hailing to go to and from transit stops? And second, what are the equity implications of such a program? In other words, do such programs boost access to transit among populations historically excluded or underserved by transportation systems? Our findings suggest that the MOD program successfully delivered thousands of riders to and from transit stations during its first year. Whether these rides were delivered to vulnerable groups with limited access to the transit system, however, is less clear. Survey results suggest that compared to transit riders as whole, program users overall were whiter and more likely to own smartphones and have bank accounts. Thus while people are clearly interested and willing to use subsidized ride-hail services to access transit, the program in its current design does not appear to meaningfully increase access for disadvantaged groups. This result may stem more from the design of the pilot itself, as opposed to suggesting the limited potential of ride-hailing more broadly to solve access problems.